Occurrence, site fidelity, and abundance of bottlenose dolphins (Tursiops truncatus) in the Western Ligurian Sea - Ascheri, Davide; Fontanesi, Elena; Ballardini , Marco; Nani, Barbara; Alessi , Jessica (J. Cetacean Res. Manage., 2022)
This study represents the first complete assessment of the population dynamics and residency of common bottlenose dolphins in the Western Ligurian Sea, an area where bottlenose dolphin sightings have been rare in the past. Despite being greatly affected by human pressure, information about this population is poor and sporadic. The study took place from April 2018 to December 2020. One hundred and seventy‐one dedicated boat surveys were performed year‐round resulting in 95 sightings, and 123 individuals were identified through mark‐recapture photo‐identification techniques. Dolphins were found to be present year‐round. Most of the animals (79) used the area sporadically and only 19.5% of the dolphins (24) were seen regularly. Bottlenose dolphin abundance was estimated at 248 using open POPAN population models (CI 95% = 217–284). These results help fill a knowledge gap by highlighting the regular presence of bottlenose dolphins in the study area. Moreover, they represent a baseline for future studies investigating abundance trends and the conservation status of this population